Risk management and insurance - Williams, C. Arthur; Heins, Richard M. (New York : McGraw-Hill, 1985)
This fifth edition is designed primarily for introductory one-semester or one-quarter courses in risk management and insurance. The text is divided into four parts. Part 1 acquaints the student with risk- its nature and its effects, and discusses the purposes and scope of risk management. Part 2, which deals with business risk management, describes the risk management function in business, how a business can identify and measure its loss exposures. Part 3 covers the unique aspects of family risk management. Part 4 deals with government regulation of insurers.
Includes bibliographical references and index.
ne 14/05/2018
Loans
Keywords: Risk management; Business insurance; Insurance